The association between pollutant levels and asthma-related emergency department visits in the Bronx after the World Trade Center attacks. (3rd October 2019) - Sharma, Kunwar Ishan; Abraham, Ryan; Mowrey, Wenzhu; Toh, Jennifer; Rosenstreich, David; Jariwala, Sunit
Abstract: Objective : To examine the potential impact of the World Trade Center (WTC) attacks on asthma-related emergency department visits (AREDV) in the New York City borough of the Bronx. Methods: We obtained daily nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ) and ozone (O3 ) values from the National Climatic Data Center's collection station in the Bronx from 1999 and 2002, a year before and after the WTC attacks. We compared daily AREDV and pollutant levels between 1999 and 2002 using the Wilcoxon signed rank sum test. We considered each season separately due to seasonal variations of AREDV and pollutants. We then used multiple linear regression models to assess the relationships between the changes in AREDV and the changes in pollutants from 1999 to 2002 in each season. Results : There were statistically significant increases from 1999 to 2002 in the daily NO2 in the summer. Significant increases for daily SO2 and O3 values from 1999 to 2002 occurred in all seasons. Significant increases occurred in daily AREDV values in the spring and fall. Multiple linear regression analyses showed that increases in the daily O3 values were significantly associated with increases in AREDV from 1999 to 2002 in the summer season. Conclusion : We observed a possible association between the WTC attacks and significant increases in O3 and SO2 for all seasons, and NO2 for the summer. AREDV significantly increased following the WTC attacks. Increases in daily O3 values were significantly associated with increases in AREDV in the summer season.